Dynamic capital structure in Indonesia: does the education and experience of CEOs matter? - Chua, Meishan; Ab Razak, Nazrul Hisyam; Md Nassir, Annuar; Yahya, Mohamed Hisham (Elsevier Taiwan LLC., 2022)
Based on the Upper Echelon Theory, this paper examined the relationship of CEO education and experience with the dynamic capital structure (DCS) using the target leverage and speed of adjustment (SOA) models. This study applied the system generalised method of moments (SYS-GMM) to the target leverage model and Ordinary Least Squares bootstrapped standard errors to the speed of adjustment model. Using the 100 Indonesian firms, two notable findings were obtained. First, the target leverage model with the inclusion of CEO characteristics yielded a 22% of the SOA towards target leverage. Both variables showed a positive relationship with the target leverage. Second, the result revealed that the improvement of CEO education and experience by one standard deviation led to an increase in the SOA by 3.37% and 0.17%. Thus, the results were consistent with the theory whereby the education and experience of the CEOs were potential determinants the DCS.